Absorption variability of the highly obscured active galactic nucleus NGC 4507. Issue 4 (25th March 2022) - Jana, Arghajit; Ricci, Claudio; Naik, Sachindra; Tanimoto, Atsushi; Kumari, Neeraj; Chang, Hsiang-Kuang; Nandi, Prantik; Chatterjee, Arka; Safi-Harb, Samar
ABSTRACT: We present a detailed study of the highly obscured active galaxy NGC 4507, performed using four Nuclear Spectroscopic Telescope Array ( NuSTAR ) observations carried out between May and August in 2015 (∼130 ks in total). Using various phenomenological and physically motivated torus models, we explore the properties of the X-ray source and those of the obscuring material. The primary X-ray emission is found to be non-variable, indicating a stable accretion during the period of the observations. We find the equatorial column density of the obscuring materials to be ∼2 × 10 24 cm −2  while the line-of-sight column density to be ∼7–8 × 10 23 cm −2 . The source is found to be deeply buried with the torus covering factor of ∼0.85. We observe variability in the line-of-sight column density on a time-scale of <35 d. The covering factor of the Compton-Thick material is found to be ∼0.35 in agreement with the results of recent X-ray surveys. From the variability of the line-of-sight column density, we estimate that the variable absorbing material is likely located either in the BLR or in the torus.